Quantitative Analysis of Face and Neck Skin Tightening by Microfocused Ultrasound With Visualization in Asians - Lu, Pei-Hsuan; Yang, Chih-Hsun; Chang, Ya-Ching (Dermatologic surgery, 2017)
Previous studies of microfocused ultrasound with visualization (MFU-V) on facial and neck laxity were largely based on masked physician assessments, histological analysis, and safety profile. More quantitative studies are needed. To evaluate the 800 treatment lines of MFU-V on skin tightening effect of face and neck in Asians using 2 quantitative analysis systems at 0, 90, and 180 days after treatment. Total 25 subjects were recruited in this prospective study. Subjects were treated with MFU-V to the face and neck using 2 different transducers: 4 MHz, 4.5-mm focal depth and 7 MHz, 3.0-mm focal depth with total 800 lines. The subjects were evaluated by skin complexion analysis and 3-dimensional imaging system at 0, 90, and 180 days. Mean brow height lift and submental lift were calculated. All 25 subjects completed treatment and received the follow-up examinations at 90 and 180 days. Two of the 25 subjects were male. Mean patient age was 53.3 years (range: 39.8-61.1 years). Wrinkles, texture, and pores were 3 variables relevant to analysis of skin laxity. Only mean wrinkles score reduction at 90 days was statistically significant (p = .0222). There was a mean 0.47 mm brow lift at 90 days (p = .0165), but there was a 0.12 mm decrease in brow height compared to baseline at 180 days (p = .6494). At 90 days, a mean 26.44 mm submental lift was noted (p = .0217). And at 180 days, a mean 13.76 mm submental lift was noted (p = .243). This study showed that the most prominent change after the 800-line MFU-V treatments in Asians was the significant submental lift at 90 days. Other noninvasive or minimally invasive treatment modalities can be considered to combine with MFU-V for the optimal treatment response. Additional MFU-V treatments can be considered 3 months after the first treatment.